Comparative study on the effect of hydrophilic and hydrophobic polymers on the dissolution rate of a poorly water soluble drug - Jiyauddin K; Sung Y. K; Samer A.D; M. Kaleemullah; Rasha S.; S. Budiasih; Jawad A; Rasny M. R.; Gamal O. E; Junainah A. H; Eddy Y.; Fadli A; et al. (International Journal of Pharmacy and Analytical Research, 2014)
Matrix tablets of controlled release systems were designed by incorporating HPMC (K100M) and Kollidon® SR polymers in order to sustain the release of ketoprofen. All the formulations were prepared by direct compression method. Various pharmaco technical evaluation tests such as uniformity of weight, diameter and thickness, hardness and friability of the tablets were determined for each formulation and the marketed reference product. The effects of different types and concentrations of polymers were also investigated. The dissolution profiles of the formulated tablets were compared to that of the marketed reference Apo-Keto SR® tablets. The in vitro release studies revealed that the release was sustained up to 12 hours in this experiment. The best formulation was selected by obtaining a similarity factor (f2) value of more than 50%, approaching 100%. The release kinetics from each formulation such as first order equation, zero order equation, Higuchi equation, equation and Korsmeyer-Peppas was also studied. The statistical results indicated that there was significant difference between each formulation and they were found to be compatible. At the same polymer content, the most sustained drug released was found to be prepared using HPMC (K100M) rather than Kollidon® SR. It was found that by increasing the polymer content, the rate of drug release decreased. The best formulation was F2 containing 20% HPMC (K100M) polymer as it showed comparable dissolution profile to the reference product with f2 value of 71.94%. The drug release determined using kinetics equations revealed that the drug release follows the diffusion mechanism.